Analisis Perilaku Konsumsi Mahasiswi Dalam Membeli Produk Skincare Perspektif Teori Konsumsi Islam Monzer Khaf (Studi Kasus Pada Mahasiswi Perbankan Syariah STAI Al-Ishlahiyah Binjai) - Rangkuti, Ririn Anjani; Sugianto, Sugianto (ITB AAS INDONESIA Surakarta, 2024)
Observing today's phenomenon, skincare products have become an option for many women to look beautiful when caring for their skin. Likewise with STAI Al-Islahiyah Binjai Sharia Banking students. Some people buy it because they need it, some because they want it. The purpose of this article is to examine female students' consumptive behavior towards skincare products and female students' consumptive behavior towards skincare products from the perspective of Monzer Khaf's Islamic consumption theory. This study includes field research with a qualitative descriptive method approach. The data in this research was collected through observation techniques, interviews and documentation studies. Data was analyzed through data reduction, data presentation, and data verification. The study findings show that the consumption behavior of female students in consuming skincare products is more based on pure lust and desires accompanied by too high expectations for skincare products, thus stimulating them to change various brands excessively and causing wastage and waste. The consumption behavior of female students from Monzer Khaf's Islamic consumption perspective is not yet fully appropriate and implemented.